Direct and Indirect Measures of Sexual Maturity Preferences Differentiate Subtypes of Child Sexual Abusers. (April 2014) - Schmidt, Alexander F.; Gykiere, Kim; Vanhoeck, Kris; Mann, Ruth E.; Banse, Rainer
To aid risk assessment, management, and treatment planning it is essential to assess child sexual abusers' deviant sexual interests (DSI) and preferences (DSP) for sex with children. However, measurement of DSI/DSP is fraught with psychometric problems. In consequence, research interest has shifted to latency-based indirect measures as a measurement approach to complement self-report and physiological assessment. Utilizing the Explicit and Implicit Sexual Interest Profile (EISIP)—a multimethod approach consisting of self-report, viewing time, and Implicit Association Test (IAT) DSI/DSP measures—we replicated phallometric DSI/DSP differences between child sexual abuser subgroups in a sample of intrafamilial, extrafamilial, and child pornography offenders. DSI/DSP was associated with recidivism risk, offense-behavioral measures of pedophilic interest, and sexual fantasizing. It also negatively correlated with antisociality. Distinguishing between child sexual abuser subtypes and being related to recidivism risk, the EISIP is a useful tool for sexual offender assessments.